Clinical and cost effectiveness of mobile phone supported self monitoring of asthma: multicentre randomised controlled trial. (23rd March 2012) - Ryan, Dermot; Price, David; Musgrave, Stan D; Malhotra, Shweta; Lee, Amanda J; Ayansina, Dolapo; Sheikh, Aziz; Tarassenko, Lionel; Pagliari, Claudia; Pinnock, Hilary
Abstract : Objective To determine whether mobile phone based monitoring improves asthma control compared with standard paper based monitoring strategies. Design Multicentre randomised controlled trial with cost effectiveness analysis. Setting UK primary care. Participants 288 adolescents and adults with poorly controlled asthma (asthma control questionnaire (ACQ) score ≥1.5) from 32 practices. Intervention Participants were centrally randomised to twice daily recording and mobile phone based transmission of symptoms, drug use, and peak flow with immediate feedback prompting action according to an agreed plan or paper based monitoring. Main outcome measures Changes in scores on asthma control questionnaire and self efficacy (knowledge, attitude, and self efficacy asthma questionnaire (KASE-AQ)) at six months after randomisation. Assessment of outcomes was blinded. Analysis was on an intention to treat basis. Results There was no significant difference in the change in asthma control or self efficacy between the two groups (ACQ: mean change 0.75 in mobile group v 0.73 in paper group, mean difference in change −0.02 (95% confidence interval −0.23 to 0.19); KASE-AQ score: mean change −4.4 v −2.4, mean difference 2.0 (−0.3 to 4.2)). The numbers of patients who had acute exacerbations, steroid courses, and unscheduled consultations were similar in both groups, with similar healthcare costs. Overall, the mobile phone service was more expensive because of the expenses of telemonitoring. Conclusions Mobile technology does not improve asthma control or increase self efficacy compared with paper based monitoring when both groups received clinical care to guidelines standards. The mobile technology was not cost effective. Trial registration Clinical Trials NCT00512837 .